Do Optimism and Self-Esteem Lead to High Academic Adjustment? A Study among First-Year College Students - Saskiya, Ulfa; Sujadi, Eko; Ahmad, Bukhari (Educational Guidance and Counseling Development Journal, 2024)
Academic adjustment is essential for first-year students to navigate the learning process smoothly. However, multiple prior studies have highlighted academic adjustment as a commonly encountered challenge. This study investigates the impact of optimism and self-esteem on the academic adjustment of novice students. Employing a quantitative survey method, 155 respondents were selected through convenience sampling. Data collection utilized the brief versions of the Personal Optimism Scale, Rosenberg Self-esteem Scale, and Academic Adjustment Scale. Linear regression was applied to test the formulated hypotheses. The outcomes indicated that both optimism and self-esteem exerted significant partial effects on academic adjustment. Concurrent testing further confirmed their combined influence on academic adjustment. These results lay a robust foundation for intervention development through guidance and counseling services aimed at enhancing optimism and self-esteem levels among first-year students to bolster their academic adjustment.